Polymer/small-molecule parallel tandem organic solar cells based on MoO sub(x)-Ag-MoO sub(x) intermediate electrodes - Lee, Soohyun; Kang, Tae Eui; Han, Donggeon; Kim, Hoyeon; Kim, Bumjoon J; Lee, Jongjin; Yoo, Seunghyup (Solar energy materials and solar cells, 2015)
Polymer/small-molecule parallel-connected tandem organic solar cells are explored as a simple platform for high-efficiency tandem solar cells that are not subject to complications associated with complex current matching or successive solution processing. In particular, MoO sub(x)/Ag/MoO sub(x) (MAM) trilayer electrodes are investigated as an intermediate electrode that connects a front subcell composed of a solution-processed bulk heterojunction of poly{2,6'-4,8-di(5-ethylhexylthienyl) benzo[1,2-b; 3,4-b] dithiophene-alt-5-dibutyloctyl-3,6-bis(5-bromothiophen-2-yl)pyrrol o [3,4-c]pyrrole-1,4-dione} (PBDTT-DPP) and the fullerene derivative [6,6]-phenyl C61-butyric acid methyl ester (PCBM) and a back subcell composed of a thermally evaporated C sub(70) layer doped with 1,1-bis-(4-bis(4-methyl-phenyl)-amino-phenyl)-cyclohexane (TAPC). The effect of each MoO sub(x) layer is analyzed in terms of both optical and electrical properties. A joint theoretical and experimental study indicates that the electric field is distributed along the cell depth such that the photogenerated current of the front subcell depends on the thickness of both MoO sub(x) layers, with a varied interference effect, and that of the back subcell depends primarily on the thickness of the adjacent MoO sub(x) layer, with a varied cavity resonance effect. Based on optimized conditions of MAM electrodes, parallel tandem hybrid organic solar cells having higher power conversion efficiency than that of single junction cells are successfully realized.